“Diagnosis of Inherited Platelet Disorders”: Update of the Interdisciplinary S2k-Guideline [] of the Permanent Pediatric Commission of the Society of Thrombosis and Haemostasis Research (GTH e.V.) - Gebetsberger, Jennifer; Knöfler, Ralf; Streif, Werner; on behalf of the ThromKid study group; Althaus, Karina; Andres, Oliver; Bakchoul, Tamam; Ballmaier, Matthias; Bergmann, Frauke; Beutel, Karin; Böckelmann, Doris; Cario, Holger; Dame, Christof; Eberl, Wolfgang; Gebhart, Johanna; Holzhauer, Susanne; Hütker, Sebastian; Jurk, Kerstin; Kehrel, Beate; Krause, Manuela; Krause, Michael; Meyer, Oliver; Mott, Kristina; Olivieri, Martin; Pavlova, Anna; Prüller, Florian; Schulze, Harald; Siegemund, Annelie; Strauß, Gabriele; Tiebel, Oliver; Wiegering, Verena; Wieland, Ivonne; Zaninetti, Carlo; Zieger, Barbara; and mandated experts from other participating professional societies; Alberio, Lorenzo; Birschman, Ingvild; Krammer-Steiner, Beate (Hämostaseologie, 2025)
Inherited platelet disorders (IPD) are a heterogeneous group of diseases causing bleeding, which are often challenging to diagnose. To improve the diagnostic process for these disorders, the ThromKidplus study group of the Permanent Pediatric Commission of the Society for Thrombosis and Haemostasis Research (GTH) has updated the AWMF Guideline for the “Diagnosis of Inherited Platelet Disorders” (AWMF Registry Number 086–003).Key updates in the guideline include a detailed diagnostic algorithm, emphasizing the use of standardized questionnaires, thorough patient history, and specific laboratory tests such as light transmission aggregometry (LTA), flow cytometry, and genetic testing. Updated guidelines for pre-analytics standardize sample preparation and handling to ensure reliable test results. Updated protocols for aggregometry and flow cytometry aim to enhance diagnostic accuracy. The integration of next-generation sequencing (NGS) provides comprehensive genetic analysis, and a new chapter on future developments highlights emerging technologies and research fields.This guideline supports the diagnosis of IPD close to the patient's residence, limits the diagnostic process to essential steps, and assists in counseling affected individuals and their families, ensuring that the diagnosis provides especially quality of life benefits to the patient.
Keywords: inherited platelet disorders; guideline; diagnosis